2013
DOI: 10.1507/endocrj.ej13-0143
|View full text |Cite
|
Sign up to set email alerts
|

Free thyroxine (FT4) and anemia in relation to drinking status of Japanese men: The Nagasaki islands study

Abstract: THE ASSOCIATION of anemia with primary hypothyroidism is well known [1,2] since the prevalence of anemia in patients with hypothyroidism has been shown to be high (20-60%) [3]. Hypothyroidism is much more frequently observed in women than men [4], in the former particularly between puberty and menopause [5], while the prevalence of anemia is also known to be higher for women than men [6] since menstruation is an acknowledged cause of anemia in women. In fact, previous studies reported that the higher percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Finally, the association between FT4 and anemia was analyzed in relation to ethanol consumption, given the known relationship existing between alcoholism and thyroid function. In a study cohort of 843 euthyroid men aged 30–89 years from the Nagasaki islands study, a significant inverse association between FT4 and risk of anemia was found only in those who did not consume ethanol [ 93 ]. Drinkers had also significantly higher Hb concentrations and lower TSH levels than nondrinkers.…”
Section: Thyroid Hormones and Anemiamentioning
confidence: 99%
“…Finally, the association between FT4 and anemia was analyzed in relation to ethanol consumption, given the known relationship existing between alcoholism and thyroid function. In a study cohort of 843 euthyroid men aged 30–89 years from the Nagasaki islands study, a significant inverse association between FT4 and risk of anemia was found only in those who did not consume ethanol [ 93 ]. Drinkers had also significantly higher Hb concentrations and lower TSH levels than nondrinkers.…”
Section: Thyroid Hormones and Anemiamentioning
confidence: 99%
“…Furthermore, we excluded bleeding and/or anesthesia as causes of death because no rabbits died on the day of the surgical procedure. The thyroidectomized rabbits did, however, exhibit several signs of hypothyroidism such as hypothermia [26], anemia [27,28], renal dysfunction [29][30][31], and dyslipidemia [32]. A previous study showed that PTU-induced hypothyroidism in rats led to severe systolic dysfunction and heart failure [33].…”
Section: Discussionmentioning
confidence: 97%
“…Эритроциты подвергаются как прямому токсическому действию этанола и продуктов его метабо-лизма, так и окислительной модификации липидной компоненты эритроцитарных мембран [1][2][3][4]. Модификация липидного бислоя сопровождается изменением морфо-логии эритроцитов, снижением гемолитиче-ской устойчивости, возможным развитием анемии, нарушением роли в поддержании адекватного иммунного ответа [5][6][7]. Пока-зано, что у больных алкоголизмом снижены значения большинства гематологических параметров [8], вместе с тем в литературе практически не освещен вопрос зависимо-сти этих показателей от клинических харак-теристик и динамики течения алкоголизма.…”
Section: Abstract: Erythrocytes Hemoglobin Hematocrit Macrocytosisunclassified